ChemInform Abstract: Copper‐Catalyzed Enantioselective Synthesis of Axially Chiral Allenes. Issue 16 (28th March 2013) - Li, Hailing; Mueller, Daniel; Guenee, Laure; Alexakis, Alexandre
Abstract This method yields axially chiral chloroallenes with good enantioselectivity, which can be further transformed to trisubstituted allenes or terminal alkynes with propargylic quarternary stereocenters.